On the Effectiveness of Exchange Rate Interventions in Emerging Markets - Daude, Christian (OECD Development Centre Working Papers, 2014)
We analyse the effectiveness of exchange rate interventions for a panel of 18 emerging market economies during the period 2003-11. Using an error-correction model approach, we find that on average intervention is effective in moving the real exchange rate in the desired direction, controlling for deviations from the equilibrium and short-term changes in fundamentals and global financial variables. Our results are robust to different samples and estimation methods. We find little evidence of asymmetries in the effect of sales and purchases, but some evidence of more effective interventions for large deviations from the equilibrium. We also explore differences across countries according to the possible transmission channels and nature of some global shocks